1983
DOI: 10.1152/jappl.1983.54.5.1303
|View full text |Cite
|
Sign up to set email alerts
|

Effect of caffeine on skeletal muscle function before and after fatigue

Abstract: We studied the effect of caffeine on voluntary and electrically stimulated contractions of the adductor pollicis muscle in five adult volunteers. Caffeine (500 mg) was administered orally in a double-blind fashion. Electrical stimulation of the ulnar nerve was performed at 10, 20, 30, 50, and 100 Hz before and after a sustained voluntary contraction held at 50% of the maximal voluntary contraction (MVC). A brief tetanus at 30 Hz was also performed to calculate relaxation rate in the fresh muscle. Contractile p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
2
5

Year Published

1986
1986
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(98 citation statements)
references
References 0 publications
6
81
2
5
Order By: Relevance
“…This finding may be considered an extension of the work of Lopes and associates who demonstrated that the drug has no effect on fatigue production in situ during a static contraction (Lopes et al, 1983). In conclusion, our data suggest caffeine in a small dose exerts no influence on muscle function at low, moderate, and high contracting velocities tested in vivo.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…This finding may be considered an extension of the work of Lopes and associates who demonstrated that the drug has no effect on fatigue production in situ during a static contraction (Lopes et al, 1983). In conclusion, our data suggest caffeine in a small dose exerts no influence on muscle function at low, moderate, and high contracting velocities tested in vivo.…”
Section: Resultssupporting
confidence: 79%
“…It has been claimed that caffeine is widely used by weight-lifters and throwers as an ergogenic aid to enhance strength and power (Brooks and Fahey, 1984). Presently, only one study known to the authors has investigated the effects of caffeine on human skeletal muscle contractile properties in vivo (Lopes et al, 1983). Lopes and associates failed to show a difference in maximal tension obtained with electrical stimulation at 100 Hz or maximal voluntary static contraction between placebo and caffeine.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, Tarnopolsky and Cupido [31], using 20 Hz stimulation, showed an increase in force generation of the tibialis anterior with caffeine. Likewise, Lopes et al [33], using 20-50 Hz stimulation, found an increase in tetanic force of the adductor pollicis after caffeine consumption. In both studies, there were no data on the influence of caffeine on a single twitch, increases in calcium flux induced by caffeine may have been small and intracellular Ca 2+ concentrations may have only been changed sufficiently to alter performance after repetitive stimulation.…”
Section: Effects Of Caffeine On Time To Exhaustionmentioning
confidence: 86%
“…Performance improvements with CHO+CAF might be explained by CAF's additional mechanisms acting centrally or peripherally (Davis et al, 2003;Lopes et al, 1983;Meyers & Cafarelli, 2005). As an example, CAF is a known adenosine antagonist that can block the perception of fatigue (Davis et al, 2003), thereby explaining the lower perceived exertion observed with CAF in another meta-analysis (Doherty & Smith, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…For example, adenosine-receptor antagonism (Davis et al, 2003) in the CNS may explain the decreased perception of effort often observed with CAF during exercise (Cole et al, 1996;Cox et al, 2002;Doherty & Smith, 2005;Jacobson, Febbraio, Arkinstall, & Hawley, 2001). Moreover, peripheral mechanisms such as improved skeletal-muscle force production may also underlie purported benefits (Lopes, Aubier, Jardim, Aranda, & Macklem, 1983;Meyers & Cafarelli, 2005). Because CHO ingestion enhances performance by supporting vital CHO metabolism and CAF potentially acts via alternative pathways (e.g., facilitating neuromuscular force production), it is tempting to speculate that CHO combined with CAF (CHO+CAF) might prove additive in augmenting endurance-exercise performance compared with CHO alone.…”
mentioning
confidence: 99%